Characteristics of transition to turbulence in a healthy thoracic aorta using large eddy simulation - Kuiyu Cheng; Shehnaz Akhtar; Kwan Yong Lee; Sang-Wook Lee (Scientific Reports)
Abstract This study employed large eddy simulation (LES) with the wall-adapting local eddy-viscosity (WALE) model to investigate transitional flow characteristics in an idealized model of a healthy thoracic aorta. The OpenFOAM solver pimpleFoam was used to simulate blood flow as an incompressible Newtonian fluid, with the aortic walls treated as rigid boundaries. Simulations were conducted for 30 cardiac cycles and ensemble averaging was employed to ensure statistically reliable results. Main hemodynamic parameters, such as velocity fields, turbulence intensity turbulent kinetic energy (TKE), oscillatory shear index (OSI) and wall shear stress (WSS), were analyzed throughout the circulatory system. Through 3D computational fluid dynamics (CFD) visualization, we explained the transition from laminar to turbulent flow and its development throughout the cardiac cycle. The results demonstrated that turbulence originates in the aortic arch following the peak systole phase and further develops in the aortic arch and descending aorta during the mid-deceleration and end-systole phases, with the maximum turbulence intensity exceeding 25%. WSS reached up to 30 Pa during the peak systole, with an average WSS of 6.5 Pa across the cardiac cycle. Low and oscillatory WSS were observed during diastole which can potentially contribute to the development of vascular diseases including, aortic dissection and atherosclerosis.